Model Dashboard Information System untuk Peningkatan Kualitas Pengelolaan Jurnal Ilmiah - Karunia Suci Lestari; Henderi Henderi (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2021)
This study aims to develop a model of dashboard information system to improve the quality of scientific journal management. The method used to develop the model of the dashboard is prototyping. The dashboard was also developed using the Pivot Table, Histogram/ Column Chart, Line Plot/ Line Chart, and Area Chart approach. For case study, the information displayed in the dashboard which from data recorded in the MAVIB Journal. The information used includes information about the score of articles that have been received, website visitor in the form of a summary report View Page Statcounter. It can be downloaded in Excel form. The Prototype Dashboard Information System and the addition of Additional Menu in OJS were made using figma, so that it becomes an illustration for designing and updating the appearance of OJS website pages. The information displayed in the dashboard is used to make decisions in order to improve the management of scientific journals. The results show that the dashboard model successfully displays strategic information, tactical information and transactional information. This information can be used by journal managers to make decisions in improving the quality of journal management.